Diseño de un proceso para producir un sustituto del cuero bovino a base de fibras naturales derivadas de la caña de azúcar. (2022)
Leather substitutes have gained great relevance over time, an example of this is the leather or synthetic leather and fabric, which could be the most representative among the substitutes, because they are used in a large number of applications in which leather is used; recently there has been research on another substitute, which is the realization of a leather or vegan leather from fibers obtained from vegetable sources (such as bamboo, fique, some fruits, etc.), which is called vegetable leather, this is made from a mixture of resins, dyes and / or binders that are deposited on the natural fibers thus obtaining the desired substitute, this process is called vegan leather, this is manufactured from a mixture of resins, dyes and / or binders that are deposited on the natural fibers thus obtaining the desired substitute, this process is called vegan leather. This process has been carried out and commercialized by companies such as Piñatex, which makes it from pineapple fibers, Fiquetex, which makes it from fique fibers, or Desserto, which makes it from nopal fibers, among other companies. The purpose of this research project was the theoretical design of a production process of a leather substitute based on natural fibers derived from sugar cane. It consisted in the theoretical characterization of leather, in order to know the ideal properties that the proposed substitute should have from sugar cane fibers, a theoretical characterization of sugar cane was also carried out, to know the properties that the fibers have before the process, Finally, a theoretical procedure was carried out describing each process carried out to obtain the substitute, which allowed knowing the pre-treatment of the fibers to make them suitable for the process, the equipment used, the operating conditions of each equipment (temperature, time, among others), the mixture proportions of resins and colorants, for a pilot plant.